Challenges in Academic Records Management in Tertiary Institutions in Ghana - Azameti, M.S.K.; Adjei, E. (International Journal of Scientific Research in Education, 2013)
The study seeks to examine challenges associated with academic records management in tertiary institutions in Ghana. This study aims to examine internal policies related to academic recordkeeping, records management practices, technology used for keeping student academic records, and the challenges institutions face in managing student records. A stratified sampling technique was used to sample 1990 respondents from public and private universities, polytechnics, and nursing and teacher training colleges. Questionnaires were used to gather data. Both descriptive and inferential statistics were used to analyse the findings of the study. This study found a significant association between the type of institution and policies for managing student academic records. This was attributed to differences in the mandate and focuses of the various categories of tertiary institutions. The adoption of internal policies is critical for controlling irregularities in record keeping in tertiary institutions. There was no significant association between the type of institution and practices to control indecencies in academic record management. This may be attributed to the ability of institutions to adopt the practices they prefer to address record security challenges. There was a significant association between the type of institution and the kind of technologies adopted to manage records keeping systems. In general, public tertiary institutions lack the logistical support required to effectively manage electronic records. Virus infection was a major threat to electronic records keeping in tertiary institutions. (PDF) Challenges in Academic Records Management in Tertiary Institutions in Ghana. Available from: https://www.researchgate.net/publication/277713712_Challenges_in_Academic_Records_Management_in_Tertiary_Institutions_in_Ghana [accessed Oct 02 2018].
Keywords: Academic records; Academic records management; Academic records systems; Records management technology; Life cycle concept; Continuum model